The prevalence of body image disorder among kindergarten children and its relationship to social anxiety - Zayoud, Lina Latif (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research aims to determine the following: - The degree of prevalence of body image disorder among kindergarten children is known in Damascus. - The prevalence of social anxiety disorder among kindergarten children is known in Damascus. Know the relationship between body image disorder and social anxiety. - - The differences between children in the disorder of the body image are defined by the variables (sex and age group(. - Differences in social anxiety among children are defined by two variables (sex and age group). The researcher adopted the descriptive and analytical method. The research concluded the following results: -A high degree of social anxiety among kindergarten children. -High degree of body image disorder among kindergarten children. - There is a statistically significant correlation between the scores of kindergarten children on the body image disorder scale and their scores on the social anxiety scale. - Predicting social anxiety in children as a dependent variable through their scores on the body image disorder scale as an independent variable. - There is no statistically significant difference between the mean scores of children on the social anxiety scale by sex variable. - There is a statistically significant difference between the mean scores of children on the social anxiety scale according to the age group variable for the benefit of children of the age group (4-6) years. The research concluded a set of proposals are: -The need to conduct outreach programs to sensitize children to the image of their bodies. - Study of the disorder of the body image in the early ages. - Organizing social events for children and encouraging them to engage in social life and family relations. هدف البحث الى تحديد الآتي: - التعرف على درجة انتشار اضطراب صورة الجسد بين أطفال الرياض في مدينة دمشق. - التعرف على درجة انتشار اضطراب القلق الاجتماعي بين أطفال الرياض في مدينة دمشق. - توضيح العلاقة بين اضطراب صورة الجسد والقلق الاجتماعي. - قياس الفروق بين الأطفال في اضطراب صورة الجسد حسب متغيري (الجنس, والفئة العمرية). - قياس الفروق في القلق الاجتماعي بين الأطفال حسب متغيري (الجنس, والفئة العمرية). وقد اعتمدت الباحثة المنهج الوصفي التحليلي, وقد اختارت الباحثة عينة البحث بطريقة العينة المتيسرة (العينة العرضية), وبلغ عدد أفراد العينة (22) طفلاً وطفلة من أطفال الرياض، وتكوّنت أدوات البحث من مقياس اضطراب صورة الجسد ومقياس القلق الاجتماعي. وخلص البحث الى النتائج الآتية: - وجود درجة مرتفعة للقلق الاجتماعي بين اطفال الرياض. - وجود درجة مرتفعة لاضطراب صورة الجسد بين اطفال الرياض. - توجد علاقة ارتباط ذات دلالة إحصائية بين درجات أطفال الرياض على مقياس اضطراب صورة الجسد ودرجاتهم على مقياس القلق الاجتماعي. - التنبؤ بالقلق الاجتماعي لدى الأطفال كمتغير تابع من خلال درجاتهم على مقياس اضطراب صورة الجسد كمتغير مستقل. - لا يوجد فرق ذو دلالة إحصائية بين متوسطي درجات الأطفال على مقياس القلق الاجتماعي حسب متغير الجنس. - يوجد فرق ذو دلالة إحصائية بين متوسطي درجات الأطفال على مقياس القلق الاجتماعي حسب متغير الفئة العمرية لمصلحة الأطفال من الفئة العمرية (4-6) سنوات. كما خلص البحث الى المقترحات الآتية: - ضرورة إجراء برامج ارشادية لتوعية الأطفال بصورة أجسادهم . - دراسة اضطراب صورة الجسد في المراحل العمرية المبكرة . - إقامة مناسبات اجتماعية للأطفال وتشجيعهم على الانخراط في الحياة الاجتماعية وعلاقات الأسرة.